2012
DOI: 10.1523/jneurosci.2846-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

The Small G Protein H-Ras in the Mesolimbic System Is a Molecular Gateway to Alcohol-Seeking and Excessive Drinking Behaviors

Abstract: Uncontrolled consumption of alcohol is a hallmark of alcohol abuse disorders, however, the central molecular mechanisms underlying excessive alcohol consumption are still unclear. Here, we report that the GTP binding protein, H-Ras in the nucleus accumbens (NAc) plays a key role in neuroadaptations that underlie excessive alcohol-drinking behaviors. Specifically, acute (15 min) systemic administration of alcohol (2.5 g/kg) leads to the activation of H-Ras in the NAc of mice, which is observed even 24 hrs later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 51 publications
0
29
1
Order By: Relevance
“…basolateral amygdala of alcoholics [111]. Importantly, data from Ron and colleagues showing that pharmaco logical inhibition of H and KRas signaling with the farnesyltransferase, FTI276, in the nucleus accum bens reduces voluntary alcohol drinking and alco hol selfadministration in rats [124] validates the RAS superfamily as pharmacogenetic targets for treatment of AUD. The high rate of KRas mutations in multi ple forms of cancer has led to the development of anti cancer drugs that target the RAS signaling system that are now under clinical trials [125].…”
Section: Ras Signalingmentioning
confidence: 94%
“…basolateral amygdala of alcoholics [111]. Importantly, data from Ron and colleagues showing that pharmaco logical inhibition of H and KRas signaling with the farnesyltransferase, FTI276, in the nucleus accum bens reduces voluntary alcohol drinking and alco hol selfadministration in rats [124] validates the RAS superfamily as pharmacogenetic targets for treatment of AUD. The high rate of KRas mutations in multi ple forms of cancer has led to the development of anti cancer drugs that target the RAS signaling system that are now under clinical trials [125].…”
Section: Ras Signalingmentioning
confidence: 94%
“…Intra-NAc infusion of lentivirus was conducted as described in (Ben Hamida et al, 2012). Mice were anesthetized using isoflurane.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was conducted as described previously (Ben Hamida et al, 2012). Specifically, mice were euthanized by CO 2 and transcardially perfused with 0.01M PBS followed by 4% paraformaldehyde (PFA) in phosphate buffer, pH 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…In the CNS, the major activators of H-Ras are GRF1 and GRF2, whereas the enzymes that stop H-Ras activity are SynGAP and neurofibromatosis type 1 (NF1) (Fernandez-Medarde & Santos, 2011;Ye & Carew, 2010). We recently found that rat-operant selfadministration of 20% alcohol results in the activation of H-Ras in the nucleus accumbens (NAc; Hamida et al, 2012). Importantly, shRNA-mediated knockdown of H-Ras in the NAc of mice or pharmacological inhibition of H-Ras activity in rats reduced excessive intake of alcohol without affecting consumption of water, quinine, saccharin, or sucrose .…”
Section: Alcohol-seeking and Excessive-drinking Behaviorsmentioning
confidence: 99%